PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MAHASISWA SEMESTER II B PADA MATA KULIAH PERKEMBANGAN PESERTA DIDIK PROGRAM STUDI PENDIDIKAN EKONOMI FPIPS IKIP PGRI BALI TAHUN AKADEMIK 2016/2017 - Ni Luh Putu Yesy Anggreni (Widyadari : Jurnal Pendidikan, 2018)
The purpose of this study (1) to determine the significant effect of students' learning motivation on the students' learning outcomes of second semester B in the learner's developmental course, (2) to know the significant effect of students' learning discipline on student learning outcomes of second semester B on (3) to know the significant effect of the significant influence of learning motivation and learning discipline together towards the students' learning outcomes of second semester B in the course of student development Economic Education Study Program of FPIPS IKIP PGRI Bali Academic Year 2016 / 2017. Hypothesis proposed in this research (1) there is a significant effect of student's motivation on student's result of second semester B in course of student development of Economic Education Study Program of FPIPS IKIP PGRI Bali Academic Year 2016/2017 (2) there is significant influence of student discipline on the results of student learning semester II B in the course of the development of learners of Economic Education Studies Program FPIPS IKIP PGRI Bali Academic Year 2016/2017 (3) there is a significant influence of motivation and discipline together towards student learning outcomes second semester B in the course the development of students of Economic Education Studies Program FPIPS IKIP PGRI Bali Academic Year 2016/2017.The method used in data processing is the method of regression analysis. In the hypothesis testing, two regression analysis is used to analyze the contribution between two independent variables and one dependent variable, and seek relative contribution (SR) between the independent variable and effective contribution (SE). Based on predictive predictive analysis results, predictors X1 (Learning Motivation) and X2 (Discipline Learning) to Y (Learning Outcomes), obtained Freg price of 14.14636. With (N-m-1) in this case db = 33/2, with a significance level of 5% Ftable value of 3.26. This means that, the regression line in the analysis is significant to be the basis of prediction because there is a significant contribution between the criterion (Y) and the predictors (X1, X2). The relative contribution (SR) in the% of each predictor is: Predictor X1 = 84.315% and Predictor X2 = 15.685% against the Y criterion in the course of Development of the Learners. Based on these results the regression line of 46.16% consisting of effective contribution of predictors X1 (Learning Motivation) = 38.92%. And the effective contribution of Predictors X2 Discipline Learning = 7.24%. While the rest equal to 53.84% influenced by other factors.